ANALISIS PENGARUH PENAMBAHAN SISAL TERHADAP SIFAT FISIK DAN MEKANIK PADA BATA RINGAN AAC (AUTOCLAVED AERATED CONCRETE) - fauzi widyawati (Hexagon, 2023)
AAC lightweight brick (Autoclaved Aeration Concrete) is a type of brick that has a lighter density compared to other types of brick in general. This type of brick is widely applied as walls in buildings. The manufacture of lightweight bricks is much modified from the materials used. As is the case with the addition of sisal fiber (Agrave sisalana) which is added to the lightweight brick mixture. Sisal fiber was added to increase the strength value of lightweight bricks. The purpose of this study was to determine the effect of adding sisal fiber to AAC-type light bricks with the variations used, namely 0%, 2%, 4%, and 6% on the physical and mechanical properties of light bricks. The addition of sisal fiber to lightweight bricks resulted in a decrease in the physical properties of AAC lightweight bricks by volume weight (BV), but the sample values of 0%, 2%, 4%, and 6% still met the standard by volume weight of lightweight bricks according to SNI 03-0349 -1989 which is 0.600-1.600 g/cm³. For the water absorption (Absorption) test the results obtained increased, this was due to the factor of the variation in the addition of fiber which was high enough so that the absorption value of water increased and the pores in the light bricks were not completely filled. For mechanical testing, namely compressive strength, the results obtained decreased, this was due to the fact that the sisal fiber experienced the phenomenon of material segregation.